First Graduated Women Architects and Urbanists in Eastern Mediterranean Europe 1900-2000. The Cases of Cyprus, Greece, and Turkey - Inés Novella Abril; Inés Sánchez de Madariaga (Feminismo/s)
This paper provides an overview of the history of the first women graduates in architecture in Cyprus, Greece, and Turkey. Based on a review of digital archives and secondary sources written by local researchers, the aim of this research is to contribute to the dissemination and valorisation of women’s work and contributions to the history of modern architecture. The three countries under study constitute one of the most interesting European peripheries from the point of view of architecture, but also from the point of view of gender studies and women’s history. Cyprus, Greece, and Turkey, with their peculiarities and differences, condense in their recent history the political and cultural milestones that clearly show the direct link between the advance of democracy and women’s rights. Similarly, all this has an impact on architecture and urban planning; from the type and focus of projects and plans that are developed as a priority, to the people who are recognised and validated by architectural culture and its historical narrative. The research reveals the barriers and alliances of the first generations of women who studied architecture in Cyprus, Greece, and Turkey. It also reveals certain trends in the way the profession is practised, almost always linked to the socio-political context of the country and the percentage of women in the profession, among other considerations. Working for public institutions is seen as a priority working environment from which many of them have been able to make great contributions to their countries, developing infrastructures, public facilities and regulatory frameworks to improve spatial standards. Housing and heritage conservation are two areas in which these generations of women have been particularly active, some of them becoming international references in this field.